Enhancement of Papaya (Carica papaya) Seedling Growth by Pranic Agriculture - Prasad, K. Nagendra; Jois, Srikanth N. (AGRIVITA, Journal of Agricultural Science, 2020)
Recently, Pranic agriculture (PA) has gained much attention since plant growth and its characteristics were improved significantly by adopting PA technique. Pranic agriculture involves the projection of prana to seeds, soil and plants to enhance their growth. The objectives were to appraise the papaya by PA treatment and to study its effect on germination and growth characteristics during early seedling stages. Papaya seeds were exposed to PA treatment and grown under greenhouse conditions and seedling growth was evaluated from 30-day-old seedlings. Non-pranic treated seeds were referred to as the control group. For Pranic group, the mean germination days, plant length, shoot length, number of leaf, leaf length, leaf diameter and seedling vigor index I and II enhanced considerably and the results were significant (p < .05) when compared to control. Thus, the PA technique helps in enhancing the growth of papaya seedlings. PA treatment could be practiced by farmers to enhance papaya growth. Further studies are needed to compare the differences in their nutritional composition and also find out the mechanism for this improved growth in pranic group. By practicing PA technique, farmers would be benefitted to enhance their crop growth.